Revisiting the initial steps of sexual development in the malaria parasite Plasmodium falciparum - Bancells, Cristina (Nat Microbiol, 2018)
Human to vector transmission of malaria requires that some blood stage parasites abandon asexual growth and convert into non-replicating sexual forms called gametocytes. The initial steps of gametocytogenesis remain largely uncharacterized. Here we studied this part of the malaria life cycle in Plasmodium falciparum using PfAP2-G, the master regulator of sexual conversion, as a marker of commitment. We demonstrate the existence of PfAP2-G-positive sexually-committed parasite stages preceding the previously known committed schizont stage. We also found that sexual conversion can occur by two different routes: the previously described route where PfAP2-G-expressing parasites complete a replicative cycle as committed forms before converting into gametocytes upon reinvasion, or a direct route with conversion within the same cycle as initial PfAP2-G expression. The latter route is linked to early PfAP2-G expression in ring stages. Re-analysis of published single-cell RNA-seq data confirmed the presence of both routes. Consistent with these results, using plaque assays we observed that, in contrast to the prevailing model, many schizonts produced mixed plaques containing both asexual parasites and gametocytes. Altogether, our results reveal unexpected features of the initial steps of sexual development and extend the current view of this part of the malaria life cycle.